2019
DOI: 10.1016/j.bbmt.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Toxicity, and Infectious Complications in Ruxolitinib-Treated Patients with Corticosteroid-Refractory Graft-versus-Host Disease after Hematopoietic Cell Transplantation

Abstract: Corticosteroid-refractory graft-versus-host disease (SR-GVHD) remains a significant source of morbidity after allogeneic hematopoietic cell transplantation. No standard therapy exists in this setting; however, recent studies have demonstrated a very promising role for ruxolitinib, an oral Janus kinase 1/2 inhibitor. With increasing evidence of efficacy for SR-GVHD, limited data exist describing complications of ruxolitinib use, specifically infectious complications during use in SR-GVHD. In this study we repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 17 publications
1
50
1
1
Order By: Relevance
“…Such infections have a profound impact on the overall health of the affected patient, resulting in significant weight loss and a requirement for enhanced nutritional support (84). Ruxolitinib (Jakavi) is approved for the treatment of a range of diseases, including splenomegaly, in patients with myelofibrosis and has been shown to be effective in the treatment of both the chronic and acute forms of the disease (38,85). Our data might suggest that the sustained administration of Rux in patients where chronic norovirus infection has been detected may exacerbate the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Such infections have a profound impact on the overall health of the affected patient, resulting in significant weight loss and a requirement for enhanced nutritional support (84). Ruxolitinib (Jakavi) is approved for the treatment of a range of diseases, including splenomegaly, in patients with myelofibrosis and has been shown to be effective in the treatment of both the chronic and acute forms of the disease (38,85). Our data might suggest that the sustained administration of Rux in patients where chronic norovirus infection has been detected may exacerbate the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Ruxolitinib is of interest in this respect, as it selectively inhibits the JAK‐STAT pathway. Murine models and adult clinical trials have demonstrated its significant benefit in the salvage therapy of steroid‐refractory GVHD . Although publications on the efficacy of ruxolitinib in adult patients with GVHD have been increasing, studies on children are relatively few …”
Section: Introductionmentioning
confidence: 99%
“…Murine models and adult clinical trials have demonstrated its significant benefit in the salvage therapy of steroid-refractory GVHD. [3][4][5] Although publications on the efficacy of ruxolitinib in adult patients with GVHD have been increasing, studies on children are relatively few. [6][7][8] Therefore, this study aimed to evaluate ruxolitinib efficacy in children with steroid-refractory acute GVHD (aGVHD) or chronic GVHD (cGVHD).…”
Section: Introductionmentioning
confidence: 99%
“…7,8 During ruxolitinib treatment, MPN cases may be complicated by opportunistic infections such as MTB and AMI, [9][10][11][12][13][14][15][16][17] pneumocystis jiroveci pneumonitis, 22 toxoplasma retinitis, 23 Cryptococcus neoformans pneumonitis, 24 and progressive multifocal leukoencephalopathy, 25 and by reactivation of latent viral infection with hepatitis B virus 26 and cytomegalovirus. 27 Thus, optimal anti-infective prophylaxis or monitoring for occult viral infection is needed with the use of ruxolitinib. 28 Our search of the English-written literature identified nine reports of MPN cases affected by MTB infection (Table 1).…”
Section: Discussionmentioning
confidence: 99%